Critical Evaluation of City Streets (Journal of Engineering, 2013)
The diverse urban spaces of the streets is an important part of the city's physicist configuration and a link between architectural and civilizational communication through time starting from the historic towns down to the contemporary cities, within the proposals of the future cities. From general observations and literature review a research problem is crystallized as some directions not arbitrary rational when expansion and the growth of cities, and other measures wrong or the existence of some incorrect actions and processes related to the cities planning as a categorizing the goals and priorities in city plan.The streets were constitute a high proportion of the total area of cities, where up to over 30% in major cities. These faults are primarily a result of considering city streets as mere path for vehicular movement While pedestrian movement comes as a left over consideration. And a clear hypothesis search through the streets and designs which are formulated in accordance with the basis of geometric and mathematical equations to achieve the highest traffic density possible per hour (C.H.L). The research paper exposes some international considerations and improvement methods in converting vehicular streets to pedestrian streets which considers step to revitalize the city street life as a social place that responds to the active and passive human needs.